The effects of multicharged ion irradiation on a polycarbonate surface. Issue 3 (3rd April 2019) - Srinadhu, E. S.; Kulkarni, D. D.; Field, D. A.; Harriss, J. E.; Sosolik, C. E.
ABSTRACT: Polycarbonate targets were irradiated with multicharged ions of argon and oxygen with kinetic energies between 375 eV and 1 keV. Scanning electron microscopy (SEM) and x-ray photoelectron spectroscopy (XPS) analysis following the irradiations showed evidence of bond-breaking at the polycarbonate surface. The extent of the ion-induced damage indicates that the ion charge state enhances the damage well beyond that observed for similar, low flux singly charged ions. A qualitative comparison with a simple description of the radius of capture for the initial transfer of electrons between the ion and surface is used to understand the multicharged ion effects.